METODE PEMBELAJARAN TOTAL PHYSICAL RESPONSE PADA PESERTA DIDIK - Thirsa Laules Purwa; Setya Yuwana; Hendratno Hendratno (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The TPR (Total Physical Response) learning method is the method that is most suitable for children. This study aims to determine the total physical response learning method for students. This research uses qualitative research with the literature review method. The literature selection technique is based on the keywords of the total physical response learning method for students. The literature comes from accredited national journals on google scholar with a publication limit of the last 10 years. The literature study technique uses a synthetic matrix based on reference sources, sample types, methods, interventions, and findings. The results in this study were obtained from as many as 12 journals. The conclusion in this study is that the total physical response method is recommended to be applied to elementary age students so that they are able to develop the ability to hear, speak, listen, and master new vocabulary through several movements that have been commanded by the teacher, so that they indirectly learn audio, visual, and tactile.